PNIPAM-immobilized gold-nanoparticles with colorimetric temperature-sensing and reusable temperature-switchable catalysis properties. Issue 47 (23rd November 2021) - Wu, Si; Lei, Lei; Xia, Yuzheng; Oliver, Susan; Chen, Xiaonong; Boyer, Cyrille; Nie, Zhiyong; Shi, Shuxian
Abstract : The temperature-responsive core–shell hybrid nanoparticles PNIPAMs-AuNP have dual-functional applications as colorimetric temperature-sensors and reusable temperature-switchable catalysts. Abstract : Multifunctional hybrid particles have been attracting tremendous interest over decades. Herein we demonstrated the functionality of poly( N -isopropylacrylamide) immobilized gold nanoparticles (PNIPAMs-AuNP) as both colorimetric temperature-sensors and reusable temperature-switchable catalysts. The hybrid nanoparticles composed of a gold core (diameter = 14.8 ± 0.2 nm) and a PNIPAM shell (thickness = 2.6 ± 0.2 nm) exhibit reversible color changes and size adjustment in aqueous dispersion upon salt and environment temperature variation. Visual observation or colorimetric monitoring of the PNIPAMs-AuNP dispersion through a UV-vis spectrometer, we were able to detect and calibrate the changes in color between red–purple–red as the environmental temperature changes. The synergetic effect of different types of salt has been systematically investigated. It is observed that the sensitivity of the colorimetric temperature-sensor could be significantly improved by adding salts (NaCl < KCl < MgCl2 ) or controlling salt concentrations. Moreover, the temperature-switchable PNIPAMs-AuNP hybrid nanoparticles were applied to catalyze the reduction reaction of 4-nitrophenol to 4-aminophenol. The reduction process can be sped-up or slowed-down by controlling the system temperature, which switches the catalytic AuNPs surface on and off as the reversible PNIPAM chains collapse (hydrodynamic size = 41 ± 1 nm) and expand (49 ± 1 nm). Moreover, the switchable catalysts can be recycled through centrifugation and reused. The polymer-engineered core–shell PNIPAMs-AuNP hybrid nanoparticles are promising to enrich the development of temperature-responsive systems such as ambient temperature alarms and smart catalysts.